Pediatric Resident Insulin Management Education (PRIME): A Single-Session Workshop Emphasizing Active Learning - Caroline Schulmeister; Ellen Laves; Jenise Wong; Abby Walch (Association of American Medical Colleges, 2023)
Introduction Insulin is a high-risk medication, and errors can lead to patient morbidity and mortality. The American Board of Pediatrics recommends that all board-certified pediatricians be able to develop an insulin management plan for patients with diabetes. A needs assessment of pediatric residents revealed low self-efficacy at developing a new subcutaneous insulin plan despite didactic instruction on the topic. Methods We created a 90-minute interactive workshop that targeted resident skills in devising subcutaneous insulin plans. Learners engaged in small-group, problem-based learning and peer teaching to promote active learning and participation. We compared self-efficacy and knowledge before and after the intervention using paired t tests and evaluated learner satisfaction. Results Twenty-eight pediatric interns participated, with 25 completing both the pre- and postworkshop surveys. The primary outcome was self-efficacy (an individual's confidence in the ability to perform a specific task in a given domain). There was a statistically significant improvement in self-efficacy at creating a new subcutaneous insulin plan ( p < .001) as well as knowledge ( p < .001) after course completion. Learners were highly satisfied with the course, with a mean overall conference quality rating of 4.8 (SD = 0.4) based on a 5-point Likert scale (1 = poor, 5 = outstanding). Discussion An interactive workshop employing active learning methods resulted in improved self-efficacy and knowledge in first-year pediatric residents. Future work is needed to determine the impact of this workshop on patient care outcomes.